Potential of Bahari, Tiram Beach Ecotourism Padang Pariaman District, West Sumatera Province - Devano, Rigo; Yoswaty, Dessy; Nasution, Syafruddin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research was conducted in April 2020 at Tiram Beach, Padang Pariaman Regency, West Sumatra Province. This study aims to determine/identify the tourism objects of Tiram Beach which are the attractions of marine ecotourism, to determine the public perception of the Tiram Beach ecotourism activities and to analyze the supporting factors for ecotourism activities on Tiram Beach. The method used in this study is a survey method and filling out a questionnaire. The research location is divided into 3 station points, namely Station I on the edge of the river estuary, Station II near the entrance to Tiram Beach, and Station III in the mangrove area. The results showed thatTiram Beach has great potential and opportunity to be developed as a marine ecotourism area. The natural beauty that is still original and natural makes a great opportunity to make Tiram Beach a marine ecotourism area. Based on the tourism suitability index, suitability value for beach tourism activities Oyster included in the very suitable category (S1), with values ranging from 84.52-95.23% and the average value is 88.09%. This value makes Tiram Beach a marine ecotourism